2013
DOI: 10.1002/pbc.24668
|View full text |Cite
|
Sign up to set email alerts
|

PET-guided biopsy with needle navigation facilitates diagnosis of angiosarcoma in neurofibromatosis type 1

Abstract: Malignant degeneration frequently arises from preexisting plexiform neurofibroma in patients with neurofibromatosis type 1 (NF1). Image guided biopsy for diagnostic purposes, such as with CT guidance, can be technically challenging in these patients, as CT cannot distinguish malignant from benign areas within the same tumor. Navigation with multi-modality (PET, CT, and ultrasound) image fusion facilitated the successful biopsy and diagnosis of angiosarcoma arising from a pelvic neurofibroma in a patient with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This early study showed that FDG uptake in gliomas is anatomically heterogeneous and regionally related to the presence of anaplasia. In 2013, Koethe et al [8] reported that PET-guided biopsy with needle navigation facilitates the diagnosis of angiosarcoma in development, PET/CT-based metabolic imaging has been integrated with standard MRI-guided stereotactic biopsy. Zhao et al [9] investigated the clinical value of intraoperative MRI coregistration combined with PET/CT for stereotactic brain biopsy.…”
Section: Brainmentioning
confidence: 99%
“…This early study showed that FDG uptake in gliomas is anatomically heterogeneous and regionally related to the presence of anaplasia. In 2013, Koethe et al [8] reported that PET-guided biopsy with needle navigation facilitates the diagnosis of angiosarcoma in development, PET/CT-based metabolic imaging has been integrated with standard MRI-guided stereotactic biopsy. Zhao et al [9] investigated the clinical value of intraoperative MRI coregistration combined with PET/CT for stereotactic brain biopsy.…”
Section: Brainmentioning
confidence: 99%
“…PET/CT has particular value in assessing subtle foci of disease recurrence within pretreated organs whose parenchyma may be distorted by prior surgery, ablation, embolization, or radiotherapy. 37 Real-time PET/ CT-guided interventions are available at specialized centers with one center demonstrating successful biopsy of 99/105 lesions in various organs that were not identifiable by other modalities. 38 The six unsuccessful biopsies were later determined to be benign by surgical exploration, suggesting a high sensitivity of this technique for malignant lesions.…”
Section: Ultrasound/positron Emission Tomography-computed Tomography mentioning
confidence: 99%
“…10,11 Furthermore, sampling error during biopsy can lead to incomplete diagnosis in these patients, a difficulty that could be overcome by PET-guided biopsy. 9 In our patient, the neurofibroma resected with MPNST and angiosarcomatous elements had an SUV of 7.5 with uniform signal intensity, and areas of angiosarcoma on final pathology were microscopic; thus, PET-guided biopsy would have been of little use. This highlights the complexity of assessing malignant transformation with imaging or biopsy.…”
Section: Discussionmentioning
confidence: 66%
“…While an increase in PET avidity on consecutive PET scans increases concern, studies differ as to whether there is an SUV that serves as a reliable cutoff for benign versus malignant tissue . Furthermore, sampling error during biopsy can lead to incomplete diagnosis in these patients, a difficulty that could be overcome by PET‐guided biopsy . In our patient, the neurofibroma resected with MPNST and angiosarcomatous elements had an SUV of 7.5 with uniform signal intensity, and areas of angiosarcoma on final pathology were microscopic; thus, PET‐guided biopsy would have been of little use.…”
Section: Discussionmentioning
confidence: 85%